2002
DOI: 10.1093/jaoac/85.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Dry Rehydratable Film Method for Rapid Enumeration of Coliforms in Foods (3M™ Petrifilm™ Rapid Coliform Count Plate): Collaborative Study

Abstract: A rehydratable dry-film plating method for coliforms in foods, the 3M™ Petrifilm™ Rapid Coliform Count plate method, was compared with the U.S. Food and Drug Administration's Bacteriological Analytical Manual method for nondairy foods and the American Public Health Association's Standard Methods for the Examination of Dairy Products (SMEDP) method for dairy foods. Six food types, vanilla ice cream, cheddar cheese, fresh refrigerated uncooked pasta, wheat flour, prepared frozen macaroni and cheese, and frozen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Petrifilm plates have been validated for use in detecting E. coli contamination of food [Curiale et al, ; Priego et al, ; Russell, ]. Two studies report that the PEC is comparable to, or more sensitive than, the MPN especially for detection of very low numbers of E. coli , providing a more accurate assessment of the actual contamination level [Kinneberg and Lindberg, ; Matner et al, ]. However, other studies found the results of the PEC to be variable [Ottaviani, ; Ingham and Moody, ; Matner et al, ; Bredie and de Boer, ; Linton et al, ; Woody et al, ; Russell, ].…”
Section: Discussionmentioning
confidence: 99%
“…Petrifilm plates have been validated for use in detecting E. coli contamination of food [Curiale et al, ; Priego et al, ; Russell, ]. Two studies report that the PEC is comparable to, or more sensitive than, the MPN especially for detection of very low numbers of E. coli , providing a more accurate assessment of the actual contamination level [Kinneberg and Lindberg, ; Matner et al, ]. However, other studies found the results of the PEC to be variable [Ottaviani, ; Ingham and Moody, ; Matner et al, ; Bredie and de Boer, ; Linton et al, ; Woody et al, ; Russell, ].…”
Section: Discussionmentioning
confidence: 99%
“…A consistent underestimation of dip slides is known (e.g. Kinneberg and Lindberg, 2002), which limits the quantitative evaluation of dip slide readings and also produced a large scatter in our data (Fig. 7).…”
Section: Discussionmentioning
confidence: 60%
“…O pH foi analisado com o auxílio de pHmêtro Mettler 340 TM conforme metodologia descrita por KINNEBERG & LINDBERG (2002).…”
Section: Obtenção E Preparação Da Própolisunclassified
“…A contagem de coliformes totais e coliformes a 45 °C foi realizada de acordo com o Official Method of Analysis (KINNEBERG & LINDBERG 2002). Para a análise de Staphylococcus coagulase positiva e Samonella sp.…”
Section: Análises Microbiológicasunclassified